Meningkatkan Kemandirian Siswa Selama Pembelajaran Daring Melalui Model Pembelajaran Virtual Pada Siswa Kelas 2 SD N Grabag 1 Kabupaten Magelang - Sekar Mayang (Prosiding University Research Colloquium, 2021)
The purpose of this research is to increase student independence during online learningthrough a virtual learning model in 2nd grade students of N Grabag 1 MagelangElementary School. This study uses Class Action Research (PTK). Total of 5 students wereselected in this study using interview techniques, questionnaires, and pasttests. Datacollection techniques in the form of questionnaires and student learning outcomes.Pasttest given to find out student conclusions during online learning with virtual model.Results in cycle I students are still less independent in learning for cycle II there is anincrease in student learning independence. Thus, with the online virtual learning modelin 2nd grade students can be applied